UNDERSTANDING UNITS AND SHIFTS - Dexqonova Irodaxon; Ahmedov A (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Units and shifts are important concepts in understanding how quantities change and are measured in various contexts, such as physics, economics, and mathematics.Units refer to the standard of measurement used to quantify a particular quantity. For example, in physics, distance can be measured in units such as meters or kilometers, while time can be measured in units such as seconds or hours. Units allow for consistent and standardized measurement of quantities, making it easier to compare and analyze different data.